Clinical and electrocardiographic characteristics of infarctional ventricular ectopic beats: An observational study. Issue 21 (May 2017) - Li, Yuechun; Zhe-Wei, Shi; Cheng, Zheng; Guang-Yi, Chen; De-Pu, Zhou; Xiao-Wei, Li; Xueqiang, Guan; Jiafeng, Lin; Peng, Chen
Abstract : Abstract: The purpose of this study was to explore the clinical and electrocardiographic characteristics of infarctional ventricular ectopic beats (IVEBs). Thirty-eight acute myocardial infarction (AMI) patients with IVEB and 109 AMI patients without IVEB were analyzed. The morphological changes of QRS complex, ST segment, and T wave were compared to IVEB with sinus rhythm from the same period and fully evolved phase. An IVEB QRS complex often revealed the right bundle branch block morphology, in addition to Q wave AMI; no-Q wave AMI also had IVEB. Single-factor analysis found that IVEB often appeared in early AMI (<6 hours), and they were more frequent in inferoposterior with/without right ventricular involvement, large area AMI and thrombolytic reperfusion than in anterior or anteroseptal myocardial infarction, small area AMI, and unthrombolytic nonreperfusion. Multifactors no conditional logistic regression analysis revealed a positive correlation between IVEB and early AMI, AMI size, Killip heart function degree, inferoposterior with/without right ventricular involvement, and thrombolytic reperfusion. The Q wave of IVEB was wider, and the ST segment elevation was higher than those of the same period in sinus rhythms. The infarctional morphological changes of IVEB could be found before the same period in sinus rhythm and elevated myocardial enzymes. IVEBs were not rare. They were useful for early diagnosis and location of AMI.